A Framework to Ensure Data Integrity and Safety - Erick Paulus; Mochamad Azmi Fauzan (Data Science: Journal of Computing and Applied Informatics, 2018)
The technology development allows people to more easily communicate and convey information. The current communication media can facilitate its users to send and receive digital data, such as text, sound or digital image. But in terms of security, communications media not always ensure the confidentiality and authentication of data traffic. Most people rely solely on the security provided by the communications media providers in securing their data, which is essentially still inadequate. This paper presents the development of a data security framework by applying the principles of cryptography and digital signatures, such as authenticity, integrity, and data confidentiality. The application is designed using the SHA-256 algorithm as digital signature, AES algorithm as file encryption, and RSA algorithm as asymmetric key in digital file distribution and signature. Then, several simulation testing was performed to ensure the robustness of the framework. Furthermore, we also evaluated the speed of framework based on CPU and memory capacity. Based on the experiment, our proposed framework can be a reliable solution for securing data in data transaction